LEGAL ASSIGNMENT OF THE RIGHT TO EDUCATION IN SOUTH OSSETIA AND TECHNICAL CHARACTERISTICS OF THE SYSTEM OF GENERAL EDUCATION IN THE CONDITIONS OF LARGE-SCALE REFORM - Maxim Trofimov; Angelina Direganova (Гуманитарные и юридические исследования)
The Republic of Abkhazia and Republic of South Ossetia currently have a special international legal status of the states unrecognized by most countries of the world. At the same time, Russia recognized the republics as independent states, and took them under its protectorate. The support of South Ossetia by the Russian Federation is actualized in the assistance in the modernizing the education system. The Constitution of the Republic of South Ossetia guarantees every person living in its territory the right to receive preschool, general and higher education regardless of sex, race and nationality. The legislation of the Republic contains a number of guarantees of realisation of this right. However, the actual situation with the right to education is such that its complete implementation is impossible without completion of the reform and modernization process of the entire education system. Since 2012 the Russian Federation has been realizing the reform of education connected with the improvement of the organizational structure of the educational complex. Similar processes were launched in the Republic of South Ossetia which was recognized by Russia in 2008. At the same time, the processes, the problems in education and the ways of their solution are similar in the subjects of the Russian Federation and South Ossetia.